Using activity-based therapy for individuals with spinal cord injury or disease: Interviews with physical and occupational therapists in rehabilitation hospitals. (4th March 2023) - Jervis Rademeyer, Hope; Gauthier, Cindy; Zariffa, José; Walden, Kristen; Jeji, Tara; McCullum, Shane; Musselman, Kristin E.
Abstract : Objective: To understand if and how physical therapists (PTs) and occupational therapists (OTs) use activity-based therapy (ABT) and its associated technologies for the rehabilitation of individuals living with spinal cord injury or disease (SCI/D) in Canadian rehabilitation hospital settings. Design: Qualitative study. Setting: Through rehabilitation hospitals participating in the Rick Hansen Spinal Cord Injury Registry, we recruited licensed OTs and PTs to participate in focus groups. Participants: Twelve PTs and ten OTs from nine sites across eight provinces participated. Outcome Measures: To inform the development of a semi-structured interview guide, we used the Theoretical Domains Framework. To analyze the data, we used interpretive description. Results: We identified three themes that influenced therapists' use of ABT and associated technologies for SCI/D rehabilitation. (1) Therapists' decision-making approach to ABT and technology. Therapist roles, site-specific dynamics and goal setting influenced decision-making. Assuming roles such as mentor, liaison and advocate led to more ABT use. Site-specific dynamics concerned levels of ABT knowledge, teamwork, and staffing. In hospital rehabilitation, there was competition between discharge and neurorecovery goals. (2) Therapist perceived individual factors. Patient factors either increased ( i.e. patients' motivation, self-advocacy) or prevented ( i.e. mourning period, tolerance) the likelihood that ABT was introduced by therapists. (3) ABT and equipment access. Technology was used for ABT in a variety of ways. Access was affected by visible (e.g. equipment cost) and invisible barriers (e.g. departmental relations). Conclusions: The use of ABT and its associated technologies in Canadian rehabilitation hospitals is variable. Ongoing education could be offered, and site-specific implementation strategies could be developed, to promote ABT use.